Strong Medium Compression in a Spheroidal Cavitation Bubble - A.A. Aganin; T.F. Khalitova (Учёные записки Казанского университета: Серия Физико-математические науки)
Strong compression of a medium inside slightly oblate and prolate spheroidal cavitation bubbles during their strong compression in an unbounded volume of liquid in the regime with radially convergent shock waves arising in the bubble is considered. A model, in which the liquid and vapor motion is governed by fluid dynamics equations, is applied. Evaporation/condensation, as well as heat conductivity of the liquid and vapor, are taken into account. Wide-range equations of state are used. The degree of medium compression inside a bubble is estimated by the number of neutrons arising in the latter. The neutron number is calculated by integral convolution. It has been shown that the degree of medium compression inside nonspherical bubbles is less than that in the spherical one due to essential differences in the focusing of shock waves. For the same reason, the degree of medium compression inside the initially slightly prolate bubble is greater than that in the initially slightly oblate one.